1996
DOI: 10.1074/jbc.271.2.946
|View full text |Cite
|
Sign up to set email alerts
|

Plasmalopsychosine of Human Brain Mimics the Effect of Nerve Growth Factor by Activating Its Receptor Kinase and Mitogen-activated Protein Kinase in PC12 Cells

Abstract: Plasmalopsychosine, a characteristic fatty aldehyde conjugate of ␤-galactosylsphingosine (psychosine) found in brain white matter, enhances p140 trk (Trk A) phosphorylation and mitogen-activated protein kinase (MAPK) activity and as a consequence induces neurite outgrowth in PC12 cells. The effect of plasmalopsychosine on neurite outgrowth and its prolonged activation of MAPK was similar to that of nerve growth factor (NGF), and the effect was specific to neuronal cells. Plasmalopsychosine was not capable of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Studies on modulatory effects, initially observed with GM3 on EGFR tyrosine kinase [1], have been extended to effects of GM1, GD1a, GD1b, and GT1b on platelet-derived growth factor receptor [21,24], GM1 and plasmalopsychosine on nerve growth factor receptor [23,25], and GM3 and sialyl-nLc4 on insulin receptors [22,26]. Therefore, such glycosphingolipid effects can be considered as common in growth factor and hormone receptors, in general (for review see [27,28]).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on modulatory effects, initially observed with GM3 on EGFR tyrosine kinase [1], have been extended to effects of GM1, GD1a, GD1b, and GT1b on platelet-derived growth factor receptor [21,24], GM1 and plasmalopsychosine on nerve growth factor receptor [23,25], and GM3 and sialyl-nLc4 on insulin receptors [22,26]. Therefore, such glycosphingolipid effects can be considered as common in growth factor and hormone receptors, in general (for review see [27,28]).…”
Section: Discussionmentioning
confidence: 99%
“…Another example is activation by PLPS of Trk A tyrosine kinase in PC12 cells, leading to enhancement of mitogen-activated protein kinase. This mimics the effect of nerve growth factor, because withdrawal of PLPS induces apoptosis (7). PLPS weakly inhibits PKC, whereas psychosine strongly inhibits PKC (3).…”
Section: Discussionmentioning
confidence: 99%
“…PLPS has the novel effect of inducing signal transduction in neuronal cells, particularly neuritogenesis in PC12 cells without addition of nerve growth factor; i.e. PLPS mimics the effect of nerve growth factor (7). During previous studies, we noticed the presence of cationic lipids having slower TLC migration rate than PLPS in human brain (3).…”
mentioning
confidence: 99%
“…(v) Neuronal cell function in brain or central nervous system is maintained by nerve growth factor (NGF) receptor or brain-derived growth factor (BDGF) receptor, whose functions are modulated by surrounding gangliosides or GSLs in glycosynapse (Mutoh et al 1995, Sakakura et al 1996, Prinetti et al 1999.…”
Section: Cell Social Function and Glycosynapsementioning
confidence: 99%